1997
DOI: 10.1172/jci119452
|View full text |Cite
|
Sign up to set email alerts
|

p53 and the hypoxia-induced apoptosis of cultured neonatal rat cardiac myocytes.

Abstract: Myocyte cell loss is a prominent and important pathogenic feature of cardiac ischemia. We have used cultured neonatal rat cardiac myocytes exposed to prolonged hypoxia as an experimental system to identify critical factors involved in cardiomyocyte death. Exposure of myocytes to hypoxia for 48 h resulted in intranucleosomal cleavage of genomic DNA characteristic of apoptosis and was accompanied by increased p53 transactivating activity and protein accumulation. Expression of p21/WAF-1/CIP-1, a well-characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
207
2
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(221 citation statements)
references
References 36 publications
11
207
2
1
Order By: Relevance
“…This suggests that mitochondria control the progression of death receptor-dependent PCD in fibroblasts and, by blocking this death pathway, cardiac fibroblasts are protected against a wide range of death stimuli. Furthermore, our data (showing resistance of cardiac fibroblasts up to 3 days from glucose and serum deprivation plus hypoxia) go beyond a previous report describing the lack of DNA degradation after 48 h of hypoxia alone (24). These findings are of pathophysiological relevance because cardiac fibroblasts play an important role in the healing of the ischemic lesion, where the drop in local oxygen tension is accompanied by a restriction in serum and glucose availability.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This suggests that mitochondria control the progression of death receptor-dependent PCD in fibroblasts and, by blocking this death pathway, cardiac fibroblasts are protected against a wide range of death stimuli. Furthermore, our data (showing resistance of cardiac fibroblasts up to 3 days from glucose and serum deprivation plus hypoxia) go beyond a previous report describing the lack of DNA degradation after 48 h of hypoxia alone (24). These findings are of pathophysiological relevance because cardiac fibroblasts play an important role in the healing of the ischemic lesion, where the drop in local oxygen tension is accompanied by a restriction in serum and glucose availability.…”
Section: Discussionsupporting
confidence: 69%
“…This observation implies that cardiac fibroblasts are able to endure and secrete the ECM that constitutes the fibrotic scar under situations that threaten survival of other cell types. Consistent with the enhanced survival potential of cardiac fibroblasts, it has been reported that these cells have reduced apoptosis and sustained proliferation during hypoxia (24), alcohol exposure (25), and oxidative stress (26,27). However, the molecular mechanisms underlying the resistance of cardiac fibroblasts to stimuli inducing cell death are presently unknown.…”
mentioning
confidence: 88%
“…44,45 However, the molecular mechanism through which hypoxia induces apoptosis is far from clear. Through microarray analysis of a neonatal rat cardiomyocyte subtracted cDNA library, we demonstrated that expression of the pro-apoptotic gene BNIP3 is dramatically upregulated during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…45 Other reports observed neonatal myocyte cell loss after 24-72 h of hypoxia. 46 In contrast, one study found that rapidly contracting neonatal cardiac myocytes have very minimal cell death for up to 5 days under hypoxic conditions. 47 Nevertheless, neonatal cardiac myocytes have been identified to be more resistant to hypoxia than adult cardiac myocytes, demonstrated by the significant myocardial apoptosis in adult mice subjected to hypoxia.…”
Section: Bnip3mentioning
confidence: 95%